2008
DOI: 10.1038/leu.2008.218
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic insight and prognostic information from standard and molecular cytogenetic studies in the BCR-ABL-negative myeloproliferative neoplasms (MPNs)

Abstract: The frequency of cytogenetic abnormalities in the Philadelphianegative myeloproliferative neoplasms (MPNs) varies from approximately 30% in primary myelofibrosis (PMF) to less than 5% in essential thrombocytosis (ET). The spectrum of aberrations is heterogeneous, ranging from gains and losses of genetic material to structural changes including unbalanced translocations. However, no specific abnormality has been identified to date. Nevertheless, such investigations can provide evidence of clonality and, as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 147 publications
(152 reference statements)
2
23
0
1
Order By: Relevance
“…4,5,7 Recently, SNP array technology has been intensively discussed as a valuable complement to metaphase cytogenetics. 8,33 We report here on the analysis of a large cohort of classic MPN patients at high resolution using Affymetrix 6.0 SNP arrays containing more than 1.8 million genomic markers. We found a highly diverse pattern of chromosomal aberrations among individual patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,7 Recently, SNP array technology has been intensively discussed as a valuable complement to metaphase cytogenetics. 8,33 We report here on the analysis of a large cohort of classic MPN patients at high resolution using Affymetrix 6.0 SNP arrays containing more than 1.8 million genomic markers. We found a highly diverse pattern of chromosomal aberrations among individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Abnormal cytogenetics were found to be frequent in PMF but less prevalent in PV and ET. 8 Some aberrations have been observed recurrently, most notably, deletions of chromosomes 20q, 13q, and 12p; trisomy 8 and 9; gains of 9p; and various translocations. [4][5][6][7] The karyotyping methods used usually detect large-scale genomic changes, but these studies did not succeed in the identification of target genes.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) classification system recognizes 4 major SM subcategories: indolent SM (ISM; little or no evidence of organ dysfunction), aggressive SM (ASM; presence of disease-related organopathy), SM associated with a clonal hematologic non-mast cell lineage disease (SM-AHNMD), and mast cell leukemia (MCL; presence of Ն 20% mast cells in BM aspirate). 2 Although we fully endorse the current classification system, it has its limitations, and we hope to initiate a constructive dialogue that may lead to a consideration for revisions.…”
Section: Proposal For a Revised Classification Of Systemic Mastocytosismentioning
confidence: 99%
“…1 Roughly one-third of the patients have an abnormal karyotype for the most part corresponding to deletions of chromosome 13, of chromosome 20q and to partial duplication of chromosome 1q. 2 Current prognostication in PMF is based on the International Prognostic Scoring System (IPSS). 3 Different studies demonstrated that individual cytogenetic abnormalities may affect survival of patients with PMF.…”
Section: Validation Of Cytogenetic-based Risk Stratification In Primamentioning
confidence: 99%
“…2016;20(10)to the mutation, thus JAK2 activating mutations may cooperate with 9/9p trisomy. It can be hypothesized that the gain-of-function of JAK2 contributes to the disease phenotype while its enhanced constitutive activation provides a proliferative advantage (Reilly et al, 2008;Campbell et al, 2006). While the timing of the JAK2 mutation is unclear, the occurrence of common trisomies and non-random chromosome deletions in these patients suggests that it may not be the initiating event, but chromosome aneuploidy and gene deletions may precede the acquisition of JAK2 mutations.…”
Section: Fusion Proteinmentioning
confidence: 99%